Characterization of Titanium Oxide Nanoparticles Obtained by Hydrolysis Reaction of Ethylene Glycol Solution of Alkoxide - Naofumi Uekawa; Naoya Endo; Keisuke Ishii; Takashi Kojima; Kazuyuki Kakegawa (Journal of Nanotechnology)
Transparent and stable sols of titanium oxide nanoparticles were obtained by heating a mixture of ethylene glycol solution of titanium tetraisopropoxide (TIP) and a NH3 aqueous solution at 368 K for 24 h. The concentration of NH3 aqueous solution affected the structure of the obtained titanium oxide nanoparticles. For NH3 aqueous solution concentrations higher than 0.2 mol/L, a mixture of anatase TiO2 nanoparticles and layered titanic acid nanoparticles was obtained. The obtained sol was very stable without formation of aggregated precipitates and gels. Coordination of ethylene glycol to Ti4+ ions inhibited the rapid hydrolysis reaction and aggregation of the obtained nanoparticles. The obtained titanium oxide nanoparticles had a large specific surface area: larger than 350 m2/g. The obtained titanium oxide nanoparticles showed an enhanced adsorption towards the cationic dye molecules. The selective adsorption corresponded to presence of layered titanic acid on the obtained anatase TiO2 nanoparticles.